The mediating role of dividend payout ratio on the effect of cash ratio and return on equity to price-earnings ratio (a study at food and beverage companies listed on the Indonesia Stock Exchange) - Survival; Hanif Rani Iswari; Wahju Wulandari; R. Nadya Shaputri (Proceeding International Conference on Accounting and Finance, 2023)
The aim of this research is to obtain empirical evidence of the ability of cash ratio, return on equity, and dividend payout ratio to influence the price-earnings ratio, either directly or through the mediation of the dividend payout ratio. The study used a purposive sampling method based on the applied criteria, generating 15 companies (40 panel data) as a result. The path analysis model was used and the data were estimated using panel data regression by applying the software of eviews ver. 12. For the mediation test, the calculation for the sobel test was employed. The results show that neither the cash ratio nor the return on equity were able to increase the dividend payout ratio. The cash ratio was able to increase the price-earnings ratio, while the return on equity and dividend payout ratio were not able to affect the price-earnings ratio. Other findings show that the dividend payout ratio was not capable of acting as a strong mediator. This research is expected to uncover and understand the problems faced by food and beverage companies, especially those related to the variables being analyzed.